(untitled) (International Journal of Language, Literacy and Translation, 2025)
Translation, as a social and linguistic phenomenon, had been investigated from various viewpoints by scholarswith different backgrounds. This paper aims at investigating the ideological impacts of the process of translationand its consequences on the representation of ideologies and cultures. In pursuing this goal, Critical DiscourseAnalysis (CDA) was found to be an accommodating tool. The theoretical structure of this research is based uponFairclough's (1989, 1995) & Farahzad’s (2007) framework. The corpus used for analysis in this research is abook and its corresponding Persian translation. The case study of this research is All the Shah's Men: AnAmerican Coup and the Roots of Middle East Terror by Stephen Kinzer (2003) translated by Shahryar Khavvajian.Examining the text and its translation from the perspectives of macro level & micro level illuminated the fact thatthe translator employed different devices to change the ideological positioning of the source texts and deviate thereaders from the route they might have taken through reading the ST toward the one they presumed it was moreideologically efficient regarding the community the book was translated for. In other words, the power andideologies have clearly influenced the translation, comparing the source text with the target one which iscompletely diverged as the situation, policies and preferred politics asked for. Translated texts appeared in acontext different from that of the source texts. A text is produced in the context of "Self" and is translated in thesetting of "Other" or at least for "Other"